Tiny Little Fly - Rosen, Michael, 1946- (Candlewick Press, 2010)
With a tramp and a roll and a swat, Great Big Elephant, Great Big Hippo, and Great Big Tiger try to capture Tiny Little Fly as he teases each one in turn.